Overcoming Student’s Speaking Skills Through Communicative Language Method for Junior High School Students - Jon Henri Prima Saragih; Kesya Saragih; Annisa Putri Butarbutar; Natalia Ayu Lestari Panjaitan; Selviana Napitupulu (Ilmu Inovasi Nusantara, 2022)
This study aims to determine the effect on vocabulary errors and correct English pronunciation using the Communicative Language Teaching Approach method. Researchers use a test result by teaching all students to be skilled in speaking English correctly and in accordance with existing rules. Data were taken from all students in the class and taught students to speak English correctly. The results showed that the students' ability to use the Communicative Language Teaching Approach method was very effective and easy to understand. All students really understand how to pronounce English properly and correctly. Therefore, it can be concluded that the students' skills in pronouncing English are very good, but some students do not understand how to pronounce English correctly according to the rules